TAX IMPLICATIONS OF FILM COPYRIGHT ROYALTIES IN THE DIGITAL ECONOMIC TRANSFORMATION - Damarani, Purnisa; Ashidiqi, Zakky; Subagio, Aulia Tazkia (UTSAHA: Journal of Entrepreneurship, 2025)
Digital economic transformation has fundamentally altered film copyright royalty distribution mechanisms, transitioning from conventional channels to cross-border digital platforms. This shift creates opportunities for creators while presenting challenges in copyright protection and taxation frameworks. This research examines film royalties as Income Tax (PPh) objects, investigates digital transformation impacts on taxation systems, and analyzes fiscal policy implications for preventing base erosion and profit shifting (BEPS) practices. The research employs qualitative methodology with descriptive-analytical techniques. Data sources include national legislative regulations, academic literature, tax court decisions, and OECD Inclusive Framework on BEPS documentation. Analysis incorporates normative examination of applicable regulations and comparative assessment of domestic and international practices. Findings demonstrate that film royalties are classified as Income Tax objects under Article 4, paragraph (1), letter h of Indonesian Income Tax Law. Taxation frameworks vary by taxpayer status: Article 23 governs domestic transactions, Article 17 addresses final settlement for individuals and entities, and Article 26 regulates cross-border transactions with potential double taxation agreement adjustments. Digital distribution complexity introduces transparency risks and double taxation concerns, necessitating adaptive policy reforms. The research concludes that taxation system alignment with digital economic dynamics is essential for ensuring legal certainty, fiscal equity, and film creators' economic rights protection. This research contributes to understanding contemporary tax policy challenges in digital content monetization and provides regulatory framework development insights for emerging economies.